PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPS DENGAN MENGGUNAKAN PENDEKATAN KONSTRUKTIVIS DI SD - Dayanti, Murni; Miaz, Yalvema; Rahmatina, Rahmatina (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
The purpose of this research is to describe the improvement of student learning outcomes in learning social scienence using a constructivist approach in class V SDN 08 Campago Ipuh on students which amounted to 21 people. The research uses qualitative and quantitative approach. The type of research is classroom action research (PTK). Student learning outcomes cycle I average 80,30 increased to 90,06 in cycle II. Thus, constructivist approach can improve students learning outcomes in IPS learning in class V SDN 08 Campago Ipuh.